Lactation Defect with Impaired Secretory Activation in AEBP1-Null Mice - Zhang, Lei (2011)
Adipocyte enhancer binding protein 1 (AEBP1) is a multifunctional protein that negatively regulates the tumor suppressor PTEN and IκBα, the inhibitor of NF-κB, through protein-protein interaction, thereby promoting cell survival and inflammation. Mice homozygous for a disrupted AEBP1 gene developed to term but showed defects in growth after birth. AEBP1⁻′⁻ females display lactation defect, which results in the death of 100% of the litters nursed by AEBP1⁻′⁻dams. Mammary gland development during pregnancy appears normal in AEBP1⁻′⁻dams; however these mice exhibit expansion of the luminal space and the appearance of large cytoplasmic lipid droplets (CLDs) in the mammary epithelial cells at late pregnancy and parturition, which is a clear sign of failed secretory activation, and accumulation of milk proteins in the mammary gland, presumably reflecting milk stasis following failed secretory activation. Eventually, AEBP1⁻′⁻mammary gland rapidly undergoes involution at postpartum. Stromal restoration of AEBP1 expression by transplanting wild-type bone marrow (BM) cells is sufficient to rescue the mammary gland defect. Our studies suggest that AEBP1 is critical in the maintenance of normal tissue architecture and function of the mammary gland tissue and controls stromal-epithelial crosstalk in mammary gland development.